ANALISIS PENGARUH MODAL KERJA TERHADAP PROFITABILITAS (STUDI EMPIRIS PADA PERUSAHAAN LQ 45 DI BURSA EFEK INDONESIA) - Sri Yuliati; Anis Mayang Sari (Media Akuntansi, 2022)
This study aims to determine the effect of working capital ratios either partially or simultaneously on profitability, with the ratios tested are cash turnover, receivable turnover, inventory turnover and Return on Investment (ROI). The statistical method used in this study is multiple linear regression and the classical assumption test is carried out first. The results showed that cash turnover has a t-count > t- table (2.426> 2.02619) which means that it has a significant effect on ROI, receivable turnover has a t-count value > t-table (2.455> 2.02619) which meaning that it has a significant effect on ROI, inventory turnover has a value of t-count > t-table (3.360> 2.02619) which means it has a significant effect on ROI. Cash turnover, receivable turnover, inventory turnover together have a significant effect on ROI with a value of f-count > f-table (14,114>2.87). Adjusted R Square value is 50,2% which means that variations in receivable turnover, cash turnover, inventory turnover can affect the company's Return on Investment (ROI) by 50,2% and the remaining 49,8% is influenced by other variables outside of this study.